The Cultural Mission of Premier Universities in East Asia - Yang, Rui (International Higher Education, 2017)
Over the past few decades East Asia has made remarkable progress in higher education development in both quantity and quality. Yet, an assessment regarding its future development is less certain. Adopting a cultural perspective, this article reports some findings from a recent research project financed by the Hong Kong Research Grants Council. It argues that the gap between Western and East Asian ideas of a university is narrowing. East Asian premier universities are making a cultural experiment to achieve an integration of both. Their efforts have global significance.